Non-flow-through static (closed chamber) method for sampling of greenhouse gases in crop production systems - Mazengo, Tumaini Erasto Robert; Zhong, Xiuli; Liu, Xiaoying; Mwema, Mwema Felix; Gill, Rubina (Frontiers in Agronomy, 2024)
Methods and procedures for measuring greenhouse gases vary in different aspects, which could dictate most of the decisions. Even within the same context of measurements, there are different techniques and procedures. This study presents a harmonized approach so that results from different studies are easily compared, and methods can be reproduced. The relevant literature on sampling has been discussed and used to establish consistency. The applied knowledge acquired during the two related field experiments, 2017-2018 and 2018-2019, has also been used to leverage the procedures. It was observed that the non-flow-through steady-state (closed or static chamber) method is the widely used method in the field for greenhouse gas measurements. Its chronological sampling’s main steps are anchor installation, upper part chamber placement, temperature recording, gas sample withdrawal, injecting the sample into the vial, flushing the syringe with air twice, upper chamber part removal from the anchor, and placement on the plot border beside the respective anchors. These leveraged procedures can ensure consistency in acquiring data for reliable results to help make informed decisions about greenhouse gas reductions.